1976
DOI: 10.2136/sssaj1976.03615995004000050030x
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Availability to Rice in Sludge‐amended Soil under “Flood” and “Nonflood” Culture

Abstract: Rice plants (Oryza sativa var. ‘Colusa’) were grown to maturity in pots containing a soil (Domino silt loam, pH 7.5, Xerollic calciorthid) amended with 1% sewage sludge enriched with variable amounts of CdSO4 ranging up to 640 µg Cd/g. Two sets of soil cultures were used, one for rice under continuous flood and the other under nonflood conditions. Grain production for rice under flood management was relatively unaffected by the Cd treatment; 25% yield decrement was associated with a treatment of 320 µg Cd/g. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1
4

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(51 citation statements)
references
References 0 publications
0
44
1
4
Order By: Relevance
“…Arao et al (2009) also reported that Cd concentrations in the soil solution were below the detection limit during the time of flooding but increased during aerobic conditions. These results can be explained by the combining of Cd with S to form CdS at low redox potential under flooding conditions (Bingham et al, 1976). Similar to the soil solution, the flooding treatment in the pot experiment resulted in higher concentrations of extractable As, though no significant difference was found for Cd.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Arao et al (2009) also reported that Cd concentrations in the soil solution were below the detection limit during the time of flooding but increased during aerobic conditions. These results can be explained by the combining of Cd with S to form CdS at low redox potential under flooding conditions (Bingham et al, 1976). Similar to the soil solution, the flooding treatment in the pot experiment resulted in higher concentrations of extractable As, though no significant difference was found for Cd.…”
Section: Discussionmentioning
confidence: 84%
“…Water management is another promising method that affects Cd and As bioavailability in soils and their subsequent uptake by rice (Arao et al, 2009;Rahaman et al, 2011;Hu et al, 2013b). When a paddy field is flooded and the soil has a low redox potential, any Cd present in the soil combines with sulfur (S) to form CdS which has low solubility in water (Bingham et al, 1976). Thus, flooding during the growing season, especially during later stages of plant growth, can effectively reduce Cd concentrations in rice grains (Arao et al, 2009;Hu et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Water management is a direct method that is effective in controlling Cd and As bioavailability in soils and uptake by rice grains (Xu et al 2008;Arao et al 2009). Under flooded conditions, the soil Eh is very low and soil sulphur (S) will potentially be reduced to S 2− , and as a result, Cd will form CdS which has very low aqueous solubility (Bingham et al 1976). In a pot experiment, it was demonstrated that flooding the soil during plant growth decreased the Cd concentrations in rice grains, whereas fast CdS oxidation when soils were drained during the grain filling stage gave high Cd in rice (Arao et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In such soils the ratio of residual Cu is between 56.1 and 68.9% whereas it is between 71.7% and 89.1% in the Chernozems where waterlogging is not expected. Periodic reduction/oxidation during waterlogged conditions and aeration in soils results in dissolution and precipitation of soil iron oxides together with progressive scavenging of bivalent metals by specific sorption and occlusion due to precipitation of re-oxidized iron (Bingham et al 1976). In contrast to copper, lead can be characterized by much lower ratios of residual Pb and by much higher variance between soil types and different horizons.…”
Section: Central European Geology 57 2014mentioning
confidence: 99%